Sustainable Waste Management Innovations in Africa: New Perspectives and Research Agenda for Improving Global Health - Ahen Frederick; Amankwah-Amoah Joseph (MDPI, 2025)
The need for green business practices and green innovations underscores a growing recognition that climate change is now an existential threat not just to population health but also to the survival of businesses that are unable to embrace green practices with a sense of urgency. This paper contributes to the literature on market violence as an inhibitor of green innovations for sustainable waste management to curb the unneeded health effects of wastes in Africa. Our purpose is to problematize received wisdom, unquestioned assumptions, and incorrect diagnosis of the sources and health consequences of various forms of wastes in Africa. Much of the discourse on this issue remains ahistorical, and that risks leaving aside a vital question of exploitative extraction. By including this 'out-of-the-box' explanation through major case references, we are able to shed light on the critical issues that have hitherto received limited attention, thus enabling us to propose useful research questions for future enquiries. We propose a framework that delineates the structural composition of costs imposed by market violence that ranges from extraction to e-waste disposal. We advocate for the engineering of policies that create conditions for doing more with less resources, eliminating waste, and recycling as crucial steps in creating sustainable waste management innovations. Additionally, we highlight a set of fundamental issues regarding enablers and inhibitors of sustainable innovations and policies for waste management worth considering for future research. These include programmed obsolescence, irresponsible extraction, production, and consumption, all seen through the theoretical lens of market violence.